2015
DOI: 10.3989/tp.2015.12160
|View full text |Cite
|
Sign up to set email alerts
|

Dating Iron Age goldwork: First direct AMS <sup>14</sup>C results from Northwestern Iberia

Abstract: 1 2This article presents the first direct radiocarbon dates for NW Iberian "Castro culture" goldwork. Three samples were taken from a melting mass and a plano-convex ingot from the so-called Recouso (Oroso, A Coruña) and Calvos de Randín (Ourense) "hoards". The study includes pXRF analysis of the pieces from both assemblages. Identification of charcoal samples allowed us to better evaluate the results. The dates point to a period late in the Second Iron Age for both assemblages. They are the first direct chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
0
8
0
3
Order By: Relevance
“…Between the fifth and fourth centuries bce , it can be observed that iron metallurgy became widespread in the northwest (González-Ruibal 2006–7, 490–91), albeit late in relation to other Atlantic territories (Hingley 1997, 14). Within the same period, there was also an exponential increase in gold production (Armada Pita & García-Vuelta 2015). Nevertheless, a significant reduction in bronze production is not documented.…”
Section: Fourth–first Centuries Bce: the Spread Of Iron And The Estab...mentioning
confidence: 95%
See 1 more Smart Citation
“…Between the fifth and fourth centuries bce , it can be observed that iron metallurgy became widespread in the northwest (González-Ruibal 2006–7, 490–91), albeit late in relation to other Atlantic territories (Hingley 1997, 14). Within the same period, there was also an exponential increase in gold production (Armada Pita & García-Vuelta 2015). Nevertheless, a significant reduction in bronze production is not documented.…”
Section: Fourth–first Centuries Bce: the Spread Of Iron And The Estab...mentioning
confidence: 95%
“…In this area, the outstanding role of the exchange and production of metal throughout prehistory has been stressed in several studies (Armada Pita et al 2008; Comendador Rey 1999; Sánchez-Palencia et al 1999). Nonetheless, despite remarkable archaeometallurgical studies (such as Armada Pita & García-Vuelta 2015; Fanjul Peraza & Marín Suárez 2006), hardly anything has been written about the influence of changes in the metallurgical scale on social organization (exceptionally Nión-Álvarez & González García forthcoming; see also González-Ruibal 2006–7, 490–96) or to assess the role of the blacksmith in these transformations over time. Therefore, this region presents an undeniable potential for exploring the links between metallurgy and society.…”
Section: Introduction: a Different Approach To Metalworkingmentioning
confidence: 99%
“…In fact, several pure-silver ingots were identified in Iron Age hillforts nearby the Outeiro de Baltar. These include seventeen plano-convex ingots from the Calvos de Randín hoard (Outeiro da Cerca hillfort) and one from the Saceda hillfort [31], given that one of the silver ingots from the Calvos de Randín hoard was radiocarbon dated through a charcoal sample to 213-88 cal BCE [32]. Given the present work, it can be interesting to note that Calvos de Randín is one of the places with alluvial cassiterite where there were concessions during the 20th century in southern Ourense.…”
Section: Metal Artefacts and Lithic Toolsmentioning
confidence: 99%
“…One key argument is that all well dated pieces point towards the end of the Iron Age (Armada and García-Vuelta, 2015). They are therefore always related to this final moment of the Iron Age under Roman pressure, and never to the supposed turning point around the 5th century BC.…”
Section: The Iron Age In the Northwestern Iberian Peninsula: An Egalimentioning
confidence: 99%